The Effect of Calligraphy as an Art Therapy Intervention Containing Religious Motifs, on the Anxiety and Depression in Adolescent Psychiatric Patients - Sarman, Abdullah (Journal of religion and health, 2023)
This research was conducted to determine the effect of calligraphy on the anxiety and depression levels of adolescent psychiatric patients. It was conducted with adolescent psychiatric patients ages 14-17 in Turkey’s Eastern Anatolia Region. They were allocated a calligraphy (n = 40) or a wait-list (n = 39) group. Those in the calligraphy group participated in 60-min calligraphy sessions for three weeks. The state anxiety levels of adolescents who applied calligraphy decreased gradually when compared with adolescents in the control group. The difference between the third-week mean post-test state anxiety scores of the adolescents in the calligraphy and control groups was significant (t = 2.34, p = .02). The trait anxiety scale and depression scale mean post-test scores of the adolescents in the calligraphy group were lower than in the control group. The difference between two groups was significant. Calligraphy can be potentially used as a beneficial method for reducing anxiety and depression.